Nopol Synthesis from Turpentine: Review of State of Art (2012)
A review about nopol synthesis is included in this contribution. The traditional methodologies include the thermal synthesis and the use of ZnCl2 asa catalyst, and the emergent processes are the heterogeneous catalytic processes. The use of catalysts based on Sn supported on mesoporous materials, as reported by the Environmental Catalysis Research Group 10 years ago, iswidely discussed. Among the reported procedures, the homogeneous catalytic processes have the disadvantage of costs associated with separation andtreatment of inorganic salts generated during the processes. The commercial alternative for nopol production by heterogeneous catalytic processes should include reduction of costs associated with the production and regeneration of the catalysts. It should also include the minimization of the solvent required for compensating the requirements of time and energy associated with the thermal process with respect to the moderate reaction conditions of the heterogeneous catalytic processes.